2019
DOI: 10.1093/pcp/pcz110
|View full text |Cite
|
Sign up to set email alerts
|

Monodehydroascorbate Reductase Plays a Role in the Tolerance of Chlamydomonas reinhardtii to Photooxidative Stress

Abstract: Monodehydroascorbate reductase (MDAR; EC 1.6.5.4) is one of the key enzymes in the conversion of oxidized ascorbate (AsA) back to reduced AsA in plants. This study investigated the role of MDAR in the tolerance of Chlamydomonas reinhardtii P.A. Dangeard to photooxidative stress by overexpression and downregulation of the CrMDAR1 gene. For overexpression of CrMDAR1 driven by a HSP70A:RBCS2 fusion promoter, the cells survived under very high-intensity light stress (VHL, 1,800 μmol�m−2�s−1), while the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In wild type, an increase in expression of APX together with MDAR, DHAR, and GR under HL condition demonstrates that ROS over-accumulation and oxidative stress can be effectively prevented via the ascorbate–glutathione cycle. We have previously identified that MDAR 18 , DHAR 19 , and GR 20 are essential for C . reinhardtii to cope with photo-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In wild type, an increase in expression of APX together with MDAR, DHAR, and GR under HL condition demonstrates that ROS over-accumulation and oxidative stress can be effectively prevented via the ascorbate–glutathione cycle. We have previously identified that MDAR 18 , DHAR 19 , and GR 20 are essential for C . reinhardtii to cope with photo-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified that monodehydroascorbate reductase (MDAR) 18 , dehydroascorbate reductase (DHAR) 19 , and glutathione reductase (GR) 20 are essential for C . reinhardtii against high light (HL) stress, but the role of APX in high light tolerance is not examined yet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the overexpression of tomato MDHAR, Arabidopsis thaliana MDHAR (AtMDHAR1), and OsMDHAR4 in transgenic plants is associated with an acquired tolerance for abiotic stressors, such as high and low temperatures, ozone, salt, polyethylene glycol, and radiation due to the improvement of redox homeostasis and photosynthesis through the co-activation of cell rescue enzymes [18,33,34]. The homologous MDHAR1 expression of Chlamydomonas reinhardtii increased cell viability by preventing lipid peroxidation given an elevated ascorbate pool under high light-induced oxidative stress, while the downregulation of the gene was associated with a decrease in cell survival due to increased hydrogen peroxide accumulation [35,36].…”
Section: Discussionmentioning
confidence: 99%